2013
DOI: 10.29333/iejme/271
|View full text |Cite
|
Sign up to set email alerts
|

What Teachers Say About Student Difficulties Solving Mathematical Word Problems in Grades 2-5

Abstract: This study investigated teachers' perspectives of difficulties students have solving mathematical word problems and causes of those difficulties. Classroom practices and strategies teachers used in their attempts to foster student problem solving success were also studied. Participants were 70 second-fifth grade teachers from 42 different schools in a south central region of the United States. Data included analyses of interview transcriptions of teachers' responses. Findings from teachers' responses showed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 26 publications
(17 reference statements)
2
13
0
Order By: Relevance
“…However, the learning of mathematics word problems and related algebraic concepts is greatly affected by students' cognitive and affective factors (Awofala, 2014;Jupri & Drijvers, 2016;Pongsakdi et al, 2019). Mathematics word problems are an area where the majority of students experience learning obstacles in secondary schools and beyond (Abdullah et al, 2014;Awofala, 2014;Dooren et al, 2018;Goulet-Lyle et al, 2020;Julius et al, 2018;Pearce et al, 2011;Sa'ad et al, 2014;Verschaffel et al, 2010Verschaffel et al, , 2020aVerschaffel et al, , 2020b. By contrast, comprehension of mathematics word problems explains relational difficulties.…”
Section: Ugandan Contextmentioning
confidence: 99%
“…However, the learning of mathematics word problems and related algebraic concepts is greatly affected by students' cognitive and affective factors (Awofala, 2014;Jupri & Drijvers, 2016;Pongsakdi et al, 2019). Mathematics word problems are an area where the majority of students experience learning obstacles in secondary schools and beyond (Abdullah et al, 2014;Awofala, 2014;Dooren et al, 2018;Goulet-Lyle et al, 2020;Julius et al, 2018;Pearce et al, 2011;Sa'ad et al, 2014;Verschaffel et al, 2010Verschaffel et al, , 2020aVerschaffel et al, , 2020b. By contrast, comprehension of mathematics word problems explains relational difficulties.…”
Section: Ugandan Contextmentioning
confidence: 99%
“…The results of previous study (Miatun & Khusna, 2020a;Pearce, Bruun, Skinner, & Lopez-Mohler, 2013;Salemeh & Etchells, 2016) showed that students' mathematics critical thinking skill was low. Meanwhile, Ariawan and Zetriuslita (2021) reported that the critical thinking skill of the students with cognitive styles independent field was categorized as very critical, while the critical thinking skill of students with cognitive style dependent field was categorized as sufficient.…”
Section: Introductionmentioning
confidence: 90%
“…However, the learning of mathematics word problems and related algebraic concepts is greatly affected by students' cognitive and affective factors (Awofala, 2014;Jupri & Drijvers, 2016;Pongsakdi et al, 2020). Research has also shown that mathematics word problems is an area where the majority of students experience learning gaps (Abdullah et al, 2014;Awofala, 2014;Dooren et al, 2018;Goulet-Lyle et al, 2020;Julius et al, 2018a;Pearce et al, 2011;Sa'ad et al, 2014;Verschaffel et al, 2010Verschaffel et al, , 2020aVerschaffel et al, , 2020b. This has generally undermined students' competence, confidence and achievement in mathematics word problems.…”
Section: Students' Attitude Towards Mathematics Word Problemsmentioning
confidence: 99%